Is debt replacing equity in regulated privatized infrastructure in developing countries? - Estache, Antonio 1957- (Policy research working paper, 2004)
"Da Silva, Estache, and Jarvela describe the evolution of the financing structure of regulated privatized utilities and transport companies. To do so, they rely on a sample of 121 utilities distributed over 16 countries, and 23 transport infrastructure operators and 23 transport services operators distributed over 23 countries. The authors show that leverage rates vary significantly across sectors, with the highest rates observed in transport and the lowest in water. Moreover, they also show that the 1997 Asia crisis led operators to adjust their financial structure differently in different regions. Overall, the evidence they present shows that debt is replacing equity in financing the investment needs of utilities and transport services in developing countries. These results raise some questions as to whether the regulator's mandate should be expanded to monitor the financial structure of companies and as to whether the international community should make a stronger commitment to more transparent regulatory accounting systems. This paper--a product of the Office of the Vice President, Infrastructure Network--is part of a larger effort in the network to generate quantitative information on infrastructure"--World Bank web site